New Insights Into Physiological and Pathophysiological Functions of Stanniocalcin 2 - Joshi, Aditya D. (Frontiers in Endocrinology, 2020)
Stanniocalcin, a glycosylated peptide hormone, first discovered in a bony fish has originally been shown to play critical role in calcium and phosphate homeostasis. Two paralogs of stanniocalcin (stc1 and stc2) identified in mammals are widely expressed in variety of tissues. This review provides historical perspective on the discovery of fish and mammalian stanniocalcin, catalogs distribution as well as expression of stc2 in tissues and provides key structural information known till date regarding mammalian stc2. Additionally, this mini review summarizes pivotal role of stc2 in calcium and phosphate regulation, cytoprotection, cell development and angiogenesis. Finally, stc2’s role as a novel marker for human cancers has also been outlined. Reviewing these studies will provide an opportunity to understand stc2’s structure, biological functions as well as key molecular pathways involving stc2, which will help us design innovative therapeutic interventions using this novel hormone.